White Paper of the Society of Computed Body Tomography and Magnetic Resonance on Dual-Energy CT, Part 1: Technology and Terminology. Issue 6 (November 2016) - Siegel, Marilyn J.; Kaza, Ravi K.; Bolus, David N.; Boll, Daniel T.; Rofsky, Neil M.; De Cecco, Carlo N.; Foley, W. Dennis; Morgan, Desiree E.; Schoepf, U. Joseph; Sahani, Dushyant V.; Shuman, William P.; Vrtiska, Terri J.; et al.
Abstract : Abstract: This is the first of a series of 4 white papers that represent Expert Consensus Documents developed by the Society of Computed Body Tomography and Magnetic Resonance through its task force on dual-energy computed tomography (DECT). This article, part 1, describes the fundamentals of the physical basis for DECT and the technology of DECT and proposes uniform nomenclature to account for differences in proprietary terms among manufacturers.